Synthesis, characterization and biological evaluations of some 5-(substituted amino alkyl)-2-{(1, 3- benzothiazole-2-yl)}-thiazolidine-4 one Mannich bases as potent antibacterial agents - Munendra Mohan Varshney, Asif Husain, Versha Percha, Neeraj Fuloria (Journal of Applied Pharmaceutical Science, 2013)
Novel Mannich bases of 5-(substituted amino alkyl)-2-{(1, 3 benzothiazole-2-yl)}-thiazolidine-4 one, are synthesized by amination at 5th position of thiazolidine ring of 2-{(1, 3 benzothiazole-2-yl)}-thiazolidine-4 one using formaldehyde and various secondary amines. The synthesized compounds have been characterized by physico-chemical and spectral analysis and screened for their in- vitro antibacterial activity against various strains of bacteria.
Keywords: Thiazolidinone, Benzothiazole, Antibacterial, Mannic